2019
DOI: 10.15728/bbr.2019.16.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Sticky Costs Behavior and Earnings Management

Abstract: This study aims to analyze the relationship between cost asymmetry (Sticky Costs) behavior and earnings management practices of Brazilian companies. The methodology refers to descriptive, documentary and quantitative research. The sample comprised 160 Brazilian companies listed on BM&FBovespa between 2008 and 2017. Multiple linear regression models were used to analyze the data. We observed that accounting profit is affected by sticky costs behavior and by earnings management practices. Total accruals and part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 22 publications
1
9
0
14
Order By: Relevance
“…This prediction is consistent with the results of Chung et al (2019) which concluded that institutional monitoring decreases the degree of cost stickiness that leads to better performance in the future. Also, the predicted negative impact of cost stickiness on earnings quality is in line with the results of Silva et al (2019) which revealed that stickiness in cost behavior has a positive impact on abnormal accruals, i.e., cost stickiness positively affects earnings management practices which means a decline in earnings quality. Consequently, the second hypothesis can be formulated as follows: H2.…”
Section: The Effect Of Cost Stickiness On Earnings Qualitysupporting
confidence: 82%
See 2 more Smart Citations
“…This prediction is consistent with the results of Chung et al (2019) which concluded that institutional monitoring decreases the degree of cost stickiness that leads to better performance in the future. Also, the predicted negative impact of cost stickiness on earnings quality is in line with the results of Silva et al (2019) which revealed that stickiness in cost behavior has a positive impact on abnormal accruals, i.e., cost stickiness positively affects earnings management practices which means a decline in earnings quality. Consequently, the second hypothesis can be formulated as follows: H2.…”
Section: The Effect Of Cost Stickiness On Earnings Qualitysupporting
confidence: 82%
“…The current research tests the effect of sticky cost behavior on earnings quality, the second and third hypotheses, by establishing the model (2) following Banker and Byzalov (2014), Balakrishnan et al (2014), Bu et al (2015), Banker et al (2016), Silva et al (2019), and Fourati et al (2020). Like Bu et al (2015), the model (2) relies on sales levels rather than changes in sales since the dependent variable is the level of scaled earnings.…”
Section: Model (2) Examining the Impact Of Sticky Cost Behavior On Earnings Qualitymentioning
confidence: 97%
See 1 more Smart Citation
“…Por fim, com base na Tabela 6, destaca-se que o gerenciamento de resultados por atividades reais está diretamente associado ao tamanho da empresa conforme Cupertino et al (2017) e Gunny (2010). Duas possíveis explicações são a capacidade das grandes empresas de produzir mais, em algum momento, para aumentar o estoque (Reis et al, 2015) e o custo político que podem levar as empresas a gerenciar os resultados, visto que estão sob maior escrutínio público e dos órgãos de regulação (Scott, 2012;Silva, Zonatto, Dal Magro, & Klann, 2019). As demais variáveis de controle (MTB e ROA) não foram significativas conforme os resultados encontrados por Reis et al (2015).…”
Section: Tabela 6: Coeficientes Das Equações Afco Add Aprod E Remunclassified
“…Pada akhirnya, laba tunai juga akan memiliki dampak yang positif (Hung et al, 2018). Penelitian pada perusahaan di Brasil yang terdaftar dalam bursa antara tahun 2008-2017 mengamati bahwa laba akuntansi juga sangat dipengaruhi oleh manajemen laba yang dilakukan perusahaan, yang disebabkan oleh biaya tetap (Silva et al, 2018). Semakin intens praktik manajemen laba, semakin besar efek dampak negatifnya pada tingkat pengembalian aset perusahaan di tahun berikutnya (Nugroho & Eko, 2011).…”
Section: Pendahuluanunclassified